Evaluasi 97 Pasien Oftalmopati Graves’ Selama 3 Tahun Menggunakan Algoritma Eugogo dan Konsensus Nasional - Claudia Hartomuljono; Syntia Nusanti (Majalah Oftalmologi Indonesia, 2021)
Introduction and Objective: Graves’ ophthalmopathy (GO) is an autoimmune disorder of the orbit that is closely associated with Graves’ diseases. Various classification system was proposed to evaluate clinical findings in GO. As controversy exists in assessment and management of GO there is a need to evaluate and improve diagnostic criteria using practical guideline. Methods: We retrospectively reviewed Graves’ ophthalmopathy patients admitted between 2016 – 2018 to neuro-ophthalmology clinic. Clinical manifestation, the activity, severity and management of the disease were assessed using EUGOGO scale and Clinical Activity Score (CAS). Result: A total of 97 GO patients included in the study. Male to female ratio is 1:2.7 which is highest in the age range of 30-50 years. The majority of patients have hyperthyroid status (41.2%) and bilateral clinical characteristics (77%). A total of 92 patients (94.8%) had visual acuity ?6/18. The most commonly reported clinical sign at the time of assessment is eyelid edema followed by conjunctival injection. Patients with mild EUGOGO status was entirely GO inactive while 5 active GO patients were of moderate-to-severe (4 patients) and 1 patient with sight-threatening GO. Patients with active GO received 1x500 mg of intravenous methylprednisolone for 3 days every week for 4 cycles where at the follow-up there was a significant decrease in CAS score by an average of 3-4 points. Conclusion: The EUGOGO classification system provides diagnostic guidance and appropriate management algorithms for GO patients. Administration of high-dose intravenous methylprednisolone in active GO is still the first choice of therapy.